2022
DOI: 10.1177/10711007211061365
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Blood Injection With Dry-Needling vs Dry-Needling Alone Treatment for Chronic Plantar Fasciitis: A Randomized Controlled Trial

Abstract: Background: Autologous blood injection (ABI) for patients with chronic plantar fasciitis has been promoted as an approach to improve outcomes over standard dry-needling approaches. The purpose of this trial was to investigate if there are improved outcomes following an ultrasonography-guided ABI compared to dry needling alone for patients with chronic plantar fasciitis. Methods: A double-blinded (participant-blinded and observer-blinded) RCT within a single clinic enrolled 90 patients with symptoms of plantar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…35 However, retrospective comparative studies showed no statistically significant difference was found between ABI and other treatment methods (ie, dry needling or extracorporeal shock-wave therapy) in terms of pain and functionality in the treatment of PF. 36,37 In the comparison of CS and ABI, similar efficacy was demonstrated in the long term, but the onset of CS effect was observed earlier, as in the comparison of CS with PRP. 16,19,33 To date, in the only study comparing PRP and ABI in the treatment of PF, no significant difference was found between the 2 methods in terms of pain and function.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…35 However, retrospective comparative studies showed no statistically significant difference was found between ABI and other treatment methods (ie, dry needling or extracorporeal shock-wave therapy) in terms of pain and functionality in the treatment of PF. 36,37 In the comparison of CS and ABI, similar efficacy was demonstrated in the long term, but the onset of CS effect was observed earlier, as in the comparison of CS with PRP. 16,19,33 To date, in the only study comparing PRP and ABI in the treatment of PF, no significant difference was found between the 2 methods in terms of pain and function.…”
Section: Discussionmentioning
confidence: 76%
“…4,12,20,26,27,29,32 Retrospective cohort analyses and histologic studies have shown that different tendon injuries heal with the ABI method. 5,16,19,30,[33][34][35][36][37] It has been suggested that the therapeutic efficacy of ABI is similar to PRP-like regenerative efficacy. Wheeler reported long-term the effectiveness of ABI in the treatment of PF.…”
Section: Discussionmentioning
confidence: 99%